JENIS INDUSTRI, KEPEMILIKAN SAHAM ASING DAN REAKSI PASAR MODAL AKIBAT SERANGAN BOM TERORIS - Utama, Cynthia Afriani; Hapsari, Lina (UI Scholars Hub, 2012)
The purpose of this study is to investigate whether the Indonesian stock market reacts to terrorist bomb attack, and whether the Indonesian stock market reaction to terrorist bomb attack is affected by industry type and foreign ownership. Using data of terrorist bomb attack from 2000 until 2006, event study test shows that generally Indonesia capital market reacts negatively to terrorist bomb attack. Further, the multiple regression analysis shows that the stock market reaction is more negative for tourism industry than other industries while foreign ownership does not influence the stock market reaction. Thus, this study corroborates previous studies showing that terrorist attack is deemed as bad news in capital market and consequently will negatively affect the investment decision (Chen dan Siem 2004).